(untitled) - 1987-; DeSena, Jack; Whitman, Mae; 1993-; Eisen, Zach Tyler; 1988-; Nickelodeon (Television network); Paramount Pictures Corporation (Hollywoood, California, 2008)
Aang faces new challenges, difficult decisions, and secrets that are revealed. Includes 21 episodes, never- before-seen features, and much more.
The painted lady --
Rating: PG-13; for sequences of strong violence, some disturbing images and suggestive material
CHV rating: PG.
Keywords: Animated television programs; friendship; Magic; Martial arts; Reincarnation; Fantasy television programs; Drama; Magic; Drama; Drama; Reincarnation; Friendship; Drama; Martial arts; Drama; Action and adventure television programs; Video recordings for the hearing impaired